Hyper-consumerism: Rethinking Virtue Ethics and Moral Solution in Contemporary Society - Kuhumba, Kevin Shijja (Journal of Sociology, Psychology and Anthropology in Practice (JSPAP), 2018)
Hyper-consumerism is a new philosophical assumption of humanity but it is worthy to ask whether it propels goodness in the society? If no, then we have to rethink about ethical education that would cultivate virtues among people in the society. This review therefore advocates a re-think of virtue ethics and moral solution in contemporary society towards hyper-consumerism. Turning to virtue ethics, it will enable a person to attain practical wisdom or prudence which is very important in deliberation including consumption choices. Here, a moral agent examines himself whether he needs to consume this or that. Additionally, virtue ethics emphasizes on cultivation of moral virtue of temperance which enables moral agents to have a sense of moderation to matters regarding pleasure. However, the virtuous life cannot be attained overnight. So, there will be an exposition to ethical education and cultivation of virtues as habit. Since the virtuous life encompasses a sense of moderation and prudence, it enables us to replace consumerism as motivated by greediness with a status of mindfulness whereby we take only what is needed for our survival while preserving the rest for the future generations. Indeed this will bring about sustainable development.